2017
DOI: 10.1038/s41598-017-02564-9
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of Interferon-β Promotor Stimulator-1 (IPS-1) Predisposes to Bronchiolitis and Asthma-like Pathology in Response to Pneumoviral Infection in Mice

Abstract: Respiratory syncytial virus (RSV)-bronchiolitis is a major cause of infant morbidity and mortality and a risk factor for subsequent asthma. We showed previously that toll-like receptor (TLR)7 in plasmacytoid dendritic cells (pDCs) is critical for protection against bronchiolitis and asthma in mice infected with pneumonia virus of mice (PVM), the mouse homolog of RSV. This lack of redundancy was unexpected as interferon-β promotor stimulator-1 (IPS-1) signalling, downstream of RIG-I-like receptor (RLR) and not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…115 Also, IFN-b has immune-modulating properties and can inhibit eosinophilic asthma-like pathophysiology in pneumovirus-infected mice. 116 Overall, RSV-induced bronchiolitis typically affects neonates at the critical time window of lung development and therefore might have long-term influences. Murine models have shown that RSV infection causes more lung damage during the proliferative stage of lung growth compared with the equilibrated stage.…”
Section: Rsv-induced Wheezing and Asthmamentioning
confidence: 99%
“…115 Also, IFN-b has immune-modulating properties and can inhibit eosinophilic asthma-like pathophysiology in pneumovirus-infected mice. 116 Overall, RSV-induced bronchiolitis typically affects neonates at the critical time window of lung development and therefore might have long-term influences. Murine models have shown that RSV infection causes more lung damage during the proliferative stage of lung growth compared with the equilibrated stage.…”
Section: Rsv-induced Wheezing and Asthmamentioning
confidence: 99%
“…IPS-1-deficient (IPS-1 −/− ) mice show severe defects in both RIG-I and MDA5 mediated induction of type I IFNs and inflammatory cytokines and were susceptible to RNA virus infection [ 174 ]. Furthermore, IPS-1 −/− mice are more susceptible to acute infection with pneumonia virus of mice (PVM) and WNV [ 176 , 177 ]. Additional studies suggest that IPS-1 signaling contributes to the recruitment of pDCs and type I IFN production, which plays a critical role in effective antiviral responses [ 176 , 177 , 178 ].…”
Section: Rig-i Like Receptors (Rlrs)mentioning
confidence: 99%
“…Asthma is a polygenic disorder, underpinned by gene-environment interactions. As individual SNP effects on disease risk are small, we elected to use knockout mice, which we have used previously to identify novel pathogenic mechanisms [34,37,47]. We believe this approach is preferable to using an extremely high inoculum in WT mice that can induce non-physiological responses and increase the potential for false positives.…”
Section: Plos Pathogensmentioning
confidence: 99%